PENGARUH MOTIVASI KERJA DAN KEPUASAN KERJA TERHADAP KINERJA GURU SMK MUHAMMADIYAH SALATIGA - Reza Ahmadiansah (INJECT (Interdisciplinary Journal of Communication), 2016)
The influence of work motivation and job satisfaction are very important in influencing the performance. This study was aimed to assess the effect of motivation and job satisfaction conducted to the teachers of Muhammadiyah Vocational School (SMK) of Salatiga performances with the total sample of 52 teachers. From the data analysis, it shows that the effect of motivation and job satisfaction to teachers performance in Muhammadiyah Vocational School (SMK) of Salatiga is significant with the significance of 0,003 0,05. Fvalue of 6,378, and effective contribution of 20,7%.